Artificial Gramicidins - Sun, Zhanhu; Barboiu, Mihail (Frontiers in Chemistry, 2019)
Gramicidin A, gA is a natural protein channel with a well-established and simple structure and function: cations and water are transported together along the channel. Importantly, the dipolar orientation of water molecules within the pore can influence the ionic translocation. The need for simple artificial systems biomimicking the gA functions has been desired and they were until last decade unknown. Several interesting papers highlighted in this minireview have been published and supramolecular systems described here can be considered as a primitive gA mimics. The dynamics of ions/water and protons confined within gA channels is difficult to be structurally analyzed and simpler artificial systems designed at the atomic level would have a crucial relevance for understanding such translocation scenarios at the molecular level. The directional ordering of confined water-wires or ions, as observed inside primitive gA channels is reminiscent with specific interactions between water and the natural gA. This dipolar orientation may induce specific dielectric properties which most probably may influence the biological recognition at bio-interfaces or translocation of charge species along artificial channel pathways.